UPAYA MENGURANGI ANGKUTAN SEDIMEN SUNGAI GARANG KOTA SEMARANG - Langlang Adi Pratama; Susilowati Susilowati; Suseno Darsono; Dwi Kurniani (Jurnal Karya Teknik Sipil, 2014)
West floodway Semarang city is one of the infrastructure for manage flood in Garang Stream. Because of sedimentation in Garang stream, decrease flow capacity. Check Dam construction is made beam for help reduce river slope so can decrease water velocity and reduce capacity sediment delivery in Garang stream. Build check dam will reduce sedimentation in downstream Garang river. From calculation fall of rain in years with Thiessen method then do hidrology analyze using HEC-HMS and get rate of flood 100 years in location in the amount of 386.9 m3/det. Analyze using USLE method get erotion number amount 1.85 mm/year (32.01 ton/ha/year), and form erotion analyze get number of sedimentation amount 2.677 ton/ha/year. Location of Pramuka check dam construction is in downstream Pramuka bridge, Pudak Payung, Semarang. With planning as following: high physical effective main dam is 4 m, depth of foundation is 1.3 m, material for buil check dam is form river rocks. Implementation check dam works need 6 month and cost two billion eight hundred ninety five thousands million rupiah(Rp 2,895,000,000).